Effects of particle clustering on the plastic deformation and damage initiation of particulate reinforced composite utilizing X-ray CT data and finite element modeling. (15th November 2018) - Nafar Dastgerdi, J.; Anbarlooie, B.; Miettinen, A.; Hosseini-Toudeshky, H.; Remes, H.
Abstract: In this paper, a new simulation technique which can include microstructural inhomogeneity of particulate reinforced composites is proposed to accurately study deformation pattern and damage mechanism in these composites. Three dimensional microstructures constructed from XCT images incorporated into finite element modeling codes with minimal approximation to capture the effects of cluster size, local volume fraction of particles in the cluster and the distance between clusters as relevant statistical quantities describing the microstructural inhomogeneity of particulate reinforced composites. A quantitative parameter as degree of clustering is defined to consider particle clustering effect. The results indicate that the damage growth rate of composite with higher degree of clustering is significantly higher than those composites with lower degree of clustering. It is found that for region with higher degree of clustering and bigger size of clusters, the von Mises stress is higher at the same loading condition and the growth rate of plastic flow is considerably higher than the other region with lower degree of clustering. Moreover, the dislocation description of deformation in two-phase materials rationalize particle clustering effect on the yield behavior of the particulate reinforced composites and the flow stress in these composites. The macroscopic stresses that lead to the initial yielding in the matrix decrease when clusters closely proximate with bigger size and higher degree of clustering.